Visual Communication Exploration Influencer Food Vloggerin Shapening Generation Z's Responses And Behavior - Yeremia Indra Putra (Pasundan Social Science Development, 2026)
This research aims to explore how visual communication from food vloggers shapes the responses and behaviors of Generation Z in Denpasar, Bali. Using a descriptive qualitative approach, this study integrates Smith's (2005) Visual Communication Theory to analyze elements such as color, framing, and presentation, alongside Hovland's (1953) SOR (Stimulus-Organism-Response) Theory to understand how visual stimuli trigger emotional and cognitive responses. The informants group consists of 11 individuals: 3 influential Bali-based food vloggers and 8 Generation Z respondents (two from each of Denpasar's four districts). Data were gathered through interviews and observations, then analyzed using the interactive model consisting of data collection, reduction, display, and conclusion drawing. The results indicate that visually appealing and creatively presented food vlogger content significantly increases the interest, attention, and decision-making of Generation Z in choosing food. This study emphasizes the importance of visual communication strategies in shaping consumer behavior in the digital era. Future research is suggested to explore different social media platforms or utilize quantitative methods to measure the impact of specific visual variables on a larger scale. This paper includes 1 table of informant data, 10 visual content images, and 5 appendixes.